Nitrogen Rate, Phosphorus, And Potassium Levels In Chrysanthemum Cultivation (Chrysanthemum Sp) At Tomohon Tourism Seeds And Agrowidya Center - Karamoy, Tesalonika P.; Rondonuwu, Jenny J.; Kawulusan, Rafli I. (Soil and Environment Journal, 2024)
This study aims to determine the nutrient content of Nitrogen, Phosphorus, and Potassium soil in chrysanthemum (Chrysanthemum Sp) cultivation at the Tomohon Seedling and Agrowidya Wisata Center. The method used in this research is a descriptive method, with working procedures including surveying the research location, taking soil samples at 3 locations, namely soil in the greenhouse Show Window planted with chrysanthemums (K1), soil in the Show Window cultivated by chrysanthemum farmers (K2) and soil without chrysanthemum plants (K3). At each location, 3 points were determined for soil sampling with a depth of 20 cm. Keywords: nutrients, nitrogen, phosphorus, potassium, chrysanthemum Abstrak Penelitian ini bertujuan untuk mengetahui kandungan hara Nitrogen, Fosfor, dan Kalium tanah pada budidaya tanaman krisan (Chrysanthemum Sp) di Balai Bibit dan Agrowidya Wisata Tomohon. Metode yang digunakan dalam penelitian ini adalah metode deskriptif, dengan prosedur kerja meliputi survei lokasi penelitian, pengambilan contoh tanah pada 3 lokasi yaitu tanah pada Show Window rumah kaca yang ditanami tanaman krisan (K1), tanah pada Show Window yang dibudidayakan oleh petani krisan (K2) dan tanah tanpa tanaman krisan (K3). Pada setiap lokasi ditentukan 3 titik untuk pengambilan contoh tanah dengan kedalaman 20 cm. Kata kunci: hara, nitrogen, fosfor, kalium, krisan